Optimization of Quenching Process In Hot Press Forming of 22mnb5 Steel For High Strength Properties - Nuraini, Aziz; S. N., Aqida (IOP Publishing, 2013)
This paper presents hot press forming of 22MnB5 steel blanks for high strength automotive components. The hot press forming was performed using Schenck press PEZ0673 machine with maximum press force of 1000 kN. Samples were square 22MnB5 blanks, of 50×60 mm dimension. A high temperature furnace was used to heat up the blanks to austenite temperature of 950oC. Samples were hold at the austenite temperature prior to forming and quenching process. Three independent controlled parameters were cooling water temperature, press holding time and flow rate of water. Pressed samples were characterized for metallographic study, hardness properties and tensile properties. Metallographic study was conducted using Meiji optical microscope. Hardness was measured using Vickers indenter with load 1000gf. From metallographic study, the hot pressed 22MnB5 boron steel samples produced lath martensitic microstructure. Hardness of hot pressed samples increased with decreasing cooling time. The yield strength and the ultimate tensile strength of samples after hot forming were between 1546 and 1923 N/mm2. These findings were important to design tailored ultra-high strength in automotive components at different process parameter settings.